2014
DOI: 10.3389/fnbeh.2014.00236
|View full text |Cite
|
Sign up to set email alerts
|

Risk-assessment and risk-taking behavior predict potassium- and amphetamine-induced dopamine response in the dorsal striatum of rats

Abstract: Certain personality types and behavioral traits display high correlations to drug use and an increased level of dopamine in the reward system is a common denominator of all drugs of abuse. Dopamine response to drugs has been suggested to correlate with some of these personality types and to be a key factor influencing the predisposition to addiction. This study investigated if behavioral traits can be related to potassium- and amphetamine-induced dopamine response in the dorsal striatum, an area hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…This observation is possibly justified by the decreased D2R, since an inverse correlation between these parameters has been demonstrated [30]. Several studies have demonstrated that increased decision-making is associated with predisposition to rewarding and addictive behaviors [43,62,81,111,118]. Our data are in agreement with the aforementioned observations since it shows that N animals have changes in the reward system, specifically in NAc D2R and DAT contents.…”
Section: Effects Of Early Exposure To Nicotine On Behaviorsupporting
confidence: 95%
See 1 more Smart Citation
“…This observation is possibly justified by the decreased D2R, since an inverse correlation between these parameters has been demonstrated [30]. Several studies have demonstrated that increased decision-making is associated with predisposition to rewarding and addictive behaviors [43,62,81,111,118]. Our data are in agreement with the aforementioned observations since it shows that N animals have changes in the reward system, specifically in NAc D2R and DAT contents.…”
Section: Effects Of Early Exposure To Nicotine On Behaviorsupporting
confidence: 95%
“…Since increased decision-making and risk assessment behaviors were related with the modulation of dopamine levels in the mesolimbic system, which leads to a higher vulnerability to drug addiction [15,43,62,81,111,118], in the present study we tested the hypothesis that maternal nicotine exposure during lactation is associated with changes in the dopaminergic and opioid signaling pathways in the brain reward system of the adult offspring, and that these alterations are associated with changes in the offspring's food preference and behavior.…”
Section: Introductionmentioning
confidence: 97%
“…The HD animals had a shorter duration in the central circle prior to alcohol access compared to the LD animals. As previous results have revealed differences in risk-taking behavior in the central circle versus on the bridge [26,39], the functional category risk taking was also divided into performance on the bridge and in the central circle, respectively. The HD animals showed a lower risk-taking behavior in central circle-related parameters compared to the LD animals.…”
Section: Behavior In Low-drinking and High-drinking Animalsmentioning
confidence: 99%
“…Increased engagement in risk-taking behaviors is found in psychiatric disorders such as BD, schizophrenia and substance abuse [15,22], and has been studied in animal models for psychiatric disorders [19,24,30,27]. Repeated amphetamine treatment was found to increase risk-taking behavior [14,34].…”
Section: Introductionmentioning
confidence: 99%